Established and Emerging Biomarker in Chronic Heart Failure (Bangladesh Heart Journal, 2023)
Background: More than one million hospital admissions each year are due to heart failure as the major diagnosis. One in six patients over 65 who visit a primary care facility complaining of dyspnea with exertion has undiagnosed HF. By far, the most thoroughly investigated, extensively used, and acknowledged biomarkers for heart failure are natriuretic peptides. B type natriuretic peptide (BNP) and its biologically inactive fragment N-terminal pro B-type natriuretic peptide (NT-ProBNP), which are both primarily released by the ventricles in response to stretching, have been suggested to be useful for determining the prognosis or disease severity of chronic heart failure in earlier studies. Uric acid levels rise in CHF primarily due to increased production and occasionally due to decreased excretion or both. Elevated uric acid levels are a sign of developing heart failure and cardiac dysfunction. Numerous studies have demonstrated a connection between morbidity and death in CHF and elevated serum uric acid levels2.Objective: To find out the relationship between on admission serum uric acid level with established prognostic factors and Biomarkers such as different classes of NYHA, LVEF, NT-PROBNP, and their prognostic significance.Methods: From April 2018 to March 2019, this study was carried out at the National Heart Foundation Hospital and Research Institute's Department of Cardiology. After considering the inclusion and exclusion criteria, 148 patients with chronic heart failure who had admission serum uric acid measurement and telephone follow-up within 30 days were included. The study patients were divided into two groups based on Serum uric acid level Group I (SUA in men